A Erosion and Sedimentation Modeling Using Delft3D in the Manikin Estuary, Kupang, East Nusa Tenggara: Manikin Estuary, Kupang, East Nusa Tenggara - Alexandro Timotius Kolo (Institut Teknologi Sepuluh Nopember (ITS), 2025)
The sedimentation and erosion of Manikin Estuary is analysed using numerical model DELFT3D. The model simulates the influence of river flow and coastal wave to induce the transport of sediment. The river flow is obtained from automatic water level data and suspended sediment is measured on site. The wave is hindcasted using spectral wave model SWAN with forcing from ERA 5 Reanalysis Data. The model is calibrated by comparing the coastline change from the model and satellite imagery. The simulation scenarios consider the combination of river discharge and waves condition in east season and west season. The simulation shows in the west season the dominant influence from high waves produces considerable erosion and sedimentation in the estuary and coastal areas, while high river discharge during the wet season has more influence on sedimentation and erosion in the river. Meanwhile, in the east season, the dominant influence from waves results in sedimentation and erosion that predominantly occurs in coastal areas even though the waves are relatively lower than the west season.